VD_FINDINFO Décision / 2014 / 1119 vom 18. Dezember 2014 - VD Tribunal cantonal (2014)
AVOCAT D'OFFICE, EXÉCUTION DES PEINES ET DES MESURES, REJET DE LA DEMANDE | 18 al. 1 LPA-VD, 18 al. 2 LPA-VD, 47 LPA-VD